2021
DOI: 10.1039/d0ma00661k
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen evolution reaction activity and underlying mechanism of perovskite electrocatalysts at different pH

Abstract: The members of the perovskite oxide family have been vastly explored for their potential as active electrocatalysts for an efficient anodic reaction (i.e. the oxygen evolution reaction, OER) of the water splitting process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 69 publications
0
38
0
Order By: Relevance
“…This double perovskite is known in the literature for its ability to accommodate a broad range of oxygen vacancies, [10] making it the ideal candidate to validate the impact of the lattice oxygen vacancies in the OER activity. Furthermore, the OER activity of PBCO nanopowder was found to linearly scale with the electrolyte pH value in alkaline environment, which is commonly taken as an indicator of the occurrence of the LOER mechanism [11] . For a detailed analysis of the average amount and distribution of oxygen atoms in the bulk PBCO samples, powder neutron diffraction has been used.…”
Section: Introductionmentioning
confidence: 99%
“…This double perovskite is known in the literature for its ability to accommodate a broad range of oxygen vacancies, [10] making it the ideal candidate to validate the impact of the lattice oxygen vacancies in the OER activity. Furthermore, the OER activity of PBCO nanopowder was found to linearly scale with the electrolyte pH value in alkaline environment, which is commonly taken as an indicator of the occurrence of the LOER mechanism [11] . For a detailed analysis of the average amount and distribution of oxygen atoms in the bulk PBCO samples, powder neutron diffraction has been used.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al further studied the catalytic performance of BSCF in water electrolytes across a wide range of pH (7−14). 180 It was found that under near-neutral pH (7−9) BSCF showed a zeroth order relationship between OER activity and pH where the conventional AEM pathway dominates, while under high alkaline pH (12−14) BSCF revealed a first-order relationship where the LOER mechanism takes over. It should be noted that the various pH conditions adopted in this study also differ in the cation or anion species, which might have an impact on the catalytic studies.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 98%
“…Nonetheless, additional investigations are required to understand the cation effect in further detail. Kim et al further studied the catalytic performance of BSCF in water electrolytes across a wide range of pH (7–14) . It was found that under near-neutral pH (7–9) BSCF showed a zeroth order relationship between OER activity and pH where the conventional AEM pathway dominates, while under high alkaline pH (12–14) BSCF revealed a first-order relationship where the LOER mechanism takes over.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%
“…15a). 116,117 However, recent studies on perovskite oxide catalysts have revealed a new OER mechanism based on the involvement of lattice oxygens in perovskite, the so-called lattice oxygen evolution reaction (LOER) mechanism (Fig. 15a).…”
Section: Perovskite and Pyrochlorementioning
confidence: 99%
“…15a). 117–119 Particularly under alkaline conditions, perovskite oxide catalysts have recently been central to the study of the LOER mechanism to improve the OER activity. Suntivich et al systematically investigated the OER activity of perovskite oxides and suggested that the e g occupancy of the 3d electron can be employed as an effective descriptor.…”
Section: Perovskite and Pyrochlorementioning
confidence: 99%